Memories and silences haunted by Fascism : Italian colonialism, MCMXXX-MCMLX - Baratieri, Daniela (Peter Lang, 2010)
pt. 1. Theatres of memory : hegemony in the structures producing culture -- The makers of Italian news in motion -- The Italian press across different political regimes -- Audiences -- pt. 2. Searching for total silence -- Cinema : a question of total silence? -- Cinema and the persistence of desire -- Newsreels : comparing Fascist and non-Fascist imaginary -- The illustrated press and the verbosity of silence -- pt. 3. Hands on memories and silences -- Hunting and the appropriation of Africa -- The myth of Italians [as] good people -- African decolonisation in the illustrated press -- Conflicting memories -- The biography of things -- A case study: Bengasi revisited -- Conclusion -- Appendix: A selection of cartoons -- Archives and databases -- Filmography